ON COMPUTATION COMPLEXITY OF HIGH-DIMENSIONAL APPROXIMATION BY DEEP RELU NEURAL NETWORKS - D˜ung, D.; Nguyen, V.K.; Thao, M.X. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2020)
We investigate computation complexity of deep ReLU neural networks for approximating functions in H\"older-Nikol'skii spaces of mixed smoothness $\Lad$ on the unit cube $\IId:=[0,1]^d$. For any function $f\in \Lad$, we explicitly construct nonadaptive and adaptive deep ReLU neural networks having an output that approximates $f$ with a prescribed accuracy $ε$, and prove dimension-dependent bounds for the computation complexity of this approximation, characterized by the size and depth of this deep ReLU neural network, explicitly in $d$ and $ε$. Our results show the advantage of the adaptive method of approximation by deep ReLU neural networks over nonadaptive one.